Seminar on Usher's Syndrome Proceedings. - Rochester School for the Deaf, NY.; Rochester School for the Deaf, NY. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
Summarized are the presentation of M. Vernon and the Comments of primary panelists from a seminar on Usher's Syndrome, a genetic disease involving congenital deafness and progressive loss of vision due to retinitis pigmentosa. The following topics are addressed: genetics today, nature of Usher's Syndrome, symptoms, prevalence, lay diagnosis for referral, medical diagnosis, treatment, prevention, public information, available rehabilitation and other services, and research. Following panelists' comments and audience questions is a bibliography of studies and reports on the topic of Usher's Syndrome. Appended are a sample parent letter and a screening form from the Rochester School for the Deaf. (SBH)
Availability: Rochester School for the Deaf, 1545 St. Paul Street, Rochester, New York 14621.
ERIC Note: Held at Rochester School for the Deaf (Rochester, New York, December 14, 1976).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Clinical Diagnosis; Conference Reports; Deaf Blind; Etiology; Genetics; Incidence; Information Dissemination; Medical Evaluation; Multiple Disabilities; Prevention; Rehabilitation; Ushers Syndrome; Collected Works, Proceedings